MARKETING COMMUNICATION IN FISH CULINARY BUSINESS IN PONDOK PATIN H.M. YUNUS RESTAURANT PEKANBARU - Nopa Ratna Sari; Ridar Hendri; Zulkarnaen Zulkarnaen (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Research on Marketing Communication at Fish Culinary Business in Pondok Patin H.M. YunusRestaurant Pekanbaru was held in Octouber 2019 at Pondok Patin H.M. YunusRestaurant Pekanbaru. This study aims to determine the marketing mix of PondokPatin restaurant, to find out the communication techniques conducted by PondokPatin H.M. Yunus all this time. To find out what obstacles are faced by PondokPatin H.M Yunus Restaurant. The method used is descriptive qualitative method.The results showed that the PondokPatinRestaurant manager carried out interpersonal marketing communications such as promoting PondokPatin by giving business cards to relations, visiting agencies directly, promoting through print media such as newspapers, internet such as Instagram social media, e-magazine, electronics such as TV, radio and outdoor media such as billboards, billboard signs. PondokPatin restaurant managers target their products to everyone but many visitors who are married and work. The purpose of marketing communication must reach the target consumers, provide information so that the public knows about the PondokPatin restaurant, where the address, price and menu are presented. Then consumers are interested in enjoying PondokPatin cuisine. The message conveyed was "No to Pekanbaru if do not to arrive PondokPatin". Managers choose internet communication, because nowadays people use the internet as a place to get information. Constraints in marketing communication are not joining grabfood and gofood because prices are rising by 20%, do not use websites because prices make websites expensive, and the environment is disturbing like guest voices, and cellphone sounds from client pockets stop the conversation for a moment. Keywords: Communication, Marketing, Pondok Patin H.M. Yunus